Al-Haq A Global History of the First Palestinian Human Rights Organization - Welchman, Lynn (University of California Press, 2021)
Established in Ramallah in 1979, al-Haq was the first Palestinian human rights organization and one of the first such organizations in the Arab world. This inside history explores how al-Haq initiated methodologies in law and practice that were ahead of its time and that proved foundational for many strands of today's human rights work in Palestine and elsewhere. Lynn Welchman looks at both al-Haq's history and legacy to explore such questions as: Why would one set up a human rights organization under military occupation? How would one go about promoting the rule of law in a Palestinian society deleteriously served by the law and with every reason to distrust those charged with implementing its protections? How would one work to educate overseas allies and activate international law in defense of Palestinian rights? This revelatory story speaks to the practice of local human rights organizations and their impact on international groups. "This book is a godsend. A perfect example of precisely the kind of research that is most needed now, at a moment when human rights have never been more delegitimized on the international stage and abuses more rampant across the Middle East and North Africa." - MARK LEVINE, author of Heavy Metal Islam: Rock, Resistance, and the Struggle for the Soul of Islam "Clear, concise, accessible, and detailed, this unique book sheds extensive light on how and why al-Haq developed as it did. And in doing so it offers original material on the Israeli occupation of the Palestinian territories, the development of the human rights movement in Palestine and globally, and the creation and management of civil society organizations." - MOUIN RABBANI, coeditor of Jadaliyya and former Senior Analyst and Special Advisor on Palestine, International Crisis Group